Evaluation of inelastic response spectra for earthquake analysis of buildings - Kuo, Jin-ljun; Wireland, Martin; Brotton, Derick M.; Karasudhi, Pisidhi; BES Engineering Corporation, R.O.C. (Bangkok : Asian Institute of Technology, 1985)
The inelastic seismic response of three reinforced concrete moment-resisting frames with different number of stories and bays as well as different fundamental periods are investigated by using different inelastic response spectra proposed in the literature which were derived from single-degree-of- freedom systems having stiffness degrading characteristics, with ductility rations of 2,3 and 5 respectively. The maximum inelastic dynamic responses are estimated first by the inelastic response spectrum method using the SAP-IV program. Subsequently, the exact response are calculated by inelastic time history analysis with a Takeda model for beams using the DRAIN-2D Program. Assuming that the design earthquake is defined in terms of a smooth elastic response spectrum, the exact responses are obtained by analyzing each frame with five sets of spectrum-compatible accelerograms followed by a statistical analysis of the maximum responses. The maximum floor displacement, interstory drift and rotational ductility ratio obtained from the inelastic response spectrum method are then compared with the corresponding maximum dynamic responses from the inelastic time history analysis. The results of the inelastic response spectrum method agree satisfactorily with the exact response and it is concluded that inelastic spectra after Newmark and Hall suitable for earthquake resistant design of building frames.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Structural dynamics; Earthquakes and building